The average and local structure of TiVCrNbDx (x=0, 2.2, 8) from total scattering and neutron spectroscopy. (15th February 2021) - Nygård, Magnus M.; Fjellvåg, Øystein S.; Sørby, Magnus H.; Sakaki, Kouji; Ikeda, Kazutaka; Armstrong, Jeff; Vajeeston, Ponniah; Sławiński, Wojciech A.; Kim, Hyunjeong; Machida, Akihiko; Nakamura, Yumiko; Hauback, Bjørn C.
Graphical abstract: Abstract: The volumetric hydrogen density of 160 kg H/m 3 in TiVCrNbH 8 is among the highest for interstitial hydrides, but the reported reversible capacity is only about 2/3 of the full theoretical capacity at room temperature. In the present work we have investigated the local structure in TiVCrNbD x, x = 0, 2.2, 8 with the aim to unravel how the remaining sites can be destabilized with respect to hydrogen/deuterium occupation using total scattering measurements and Reverse Monte Carlo (RMC) structure modelling. Our analysis indicates that the partially desorbed deuteride ( x = 2.2 ) adopts a body-centred tetragonal structure ( I 4 / m m m ) where the deuterium atoms occupy both tetrahedral and octahedral interstices with low occupancies. There is a significantly higher portion of occupied sites with nearest-neighbour metals with low valence-electron concentration VEC . This observation is used to motivate strategies for further destabilization of the hydride. Inelastic neutron scattering (INS) and density functional theory (DFT) calculations indicate that the vibrational density of states is very diverse in TiVCrNbH 2.4, and it is suggested that the hydrogen atoms might be mobile between nearby interstices.